CORRELATION AND GENETIC ANALYSES OF DIFFERENT CHARACTERISTICS IN SAUDI ARABIAN WHEAT REVEAL CORRELATION NETWORKS AND SEVERAL TRAIT-ASSOCIATED MARKERS - M. A. Alshehri1; Othman Alzahrani; A. T. Aziza; A. Alasmari; S. Ibrahim; O. Bahattab; Gamal Osman; A. K. Alshamari; S. A Alduaydi (Journal of Animal and Plant Sciences, 2020)
Thirty-six different morpho-agronomic traits in 40 different accessions of Saudi Arabian wheat were investigated through marker-trait association analysis, which could provide a single PCR marker. A total of 25 different correlations were retrieved, among which, days to heading (DH) was negatively correlated with flag leaf anthocyanin (FLA) (r = –0.73) and positively correlated with plant height (PH) (r = 0.63) and leaf length (LL) (r =0.62). Additionally, seeds count on spike (SCS) was positively correlated with awn color (AC) (r = 0.67) and spike color (SC) (r = 0.61) and negatively correlated with grain shape (GS) (r = –0.6). Additionally, 19 PCR primers belonging to three different types of markers (ISSR, SSR, and SCoT) were used to study the population structure and diversity and to investigate the association between different agronomic traits. The total number of bands (TNB) produced by different molecular marker assays was 158. The number of polymorphic bands (PB) ranged from 1 (SCoT3 and SSR14) to 10 (SCoT5, and SCoT35), with a mean of 4.7 bands per primer. The polymorphism percentage (PP) for primers ranged from 14% (SCoT3) to 100% (SSR9, SSR10, and SSR2), with an average of 60% per primer. Thirty-seven molecular markers (7 SSRs, 26 SCoTs, and 4 ISSRs) manifested significant associations with 29 wheat plant traits. Some markers were associated with more than one agronomic trait. These findings could support Saudi Arabian wheat breeding programs by providing several markers associated with agronomic traits that could be used in marker-assisted selection in local wheat accessions.
Keywords: Wheat; SSR; SCoT; ISSR; Saudi wheat; traits correlation; marker-assisted selection